Identifying Student’s Interests through Courses at English Department of Universitas Prima Indonesia - Azizah Husda; Lisna Kristina Eka Pandiangan; Friska Naomi Sirait; Nopita Kristina Panjaitan (RIRAI Publisher, 2022)
This study aims to analyze students' interests in towards courses at English Department of Universitas Prima Indonesia in Medan. This qualitative study uses a case study design involving 60 students in the 5th semester of the Academic Year 2018 as participants. Data are obtained through questionnaires and interviews, thus the results showed that students have higher interests in the courses of teaching and education than other variety of courses taught in the English Department. The second interest was found in language skill courses. The reasons were to determine their future goals as teachers as well as the major program decision. Students argued that the majors they chose were following their interests, but some students were still unsure about the majors and interests they had chosen. This study suggests that lecturers should motivate the students to strengthen their competences particularly to identify the students’ interests in teaching or any other goals.